Energy Policy and Security under Climate Change - Proedrou, Filippos (Springer International Publishing, 2018)
'A very topical contribution that integrates mainstream energy and ecological economics literature to establish a novel energy policy framework. The author not only showcases the merits of a steady-state energy policy for climate change mitigation and energy security, but also masterfully navigates through the implications of such a shift for world politics and the global society in the 21st century. This book is invaluable for energy and International Relations scholars and policy-makers alike. -Christos A. Frangonikolopoulos, Aristotle University, Greece This book analyses the trilemma between growth, energy security and climate change mitigation and, breaking from scholarly orthodoxy, challenges the imperative that growth must always come first. It sets forth the argument that a steady-state approach is a more appropriate conceptual mindset to enable energy transition, sets out a steady-state energy policy, and assesses the projected outcomes of its implementation in the realms of energy security, geopolitics and development. By exploring in depth the implications of such a shift, the book aims to demonstrate its positive effects on sustainability, supply security and affordability; to showcase the more favorable geopolitics of renewable energy; and to unpack new pathways towards development. By bringing together ecological economics and mainstream energy politics, fresh insight to energy and climate policy is provided, alongside their broader geopolitical and developmental ramifications. Filippos Proedrou is Research Fellow in Social Policy (International Affairs) at the University of South Wales, UK. His areas of expertise are energy policy and security, geopolitics, EU studies, Russian foreign policy and ecological economics. He has published extensively in these fields.